Pengaruh Dosis Pupuk Mitra Flora dan Ekstrak Daun Kelor (Moringa oleifera) Terhadap Pertumbuhan dan Hasil Tanaman Sawi (Brassica juncea L.) - Heriberta Banu; Roberto I. C. O. Taolin; Maria Afnita Lelang (Fakultas Pertanian, Universitas Timor, 2016)
This study aims to determine the effect of liquid fertilizer Mitra Flora and moringa leaf extract on the growth and yield of mustard and to know the dose of liquid fertilizer Mitra Flora and moringa leaf extract that is appropriate for the growth and yield of mustard greens. The design used was factorial randomized block design with 3 replications. The first factor is Mitra Flora fertilizer dosage consists of three levels ie without liquid fertilizer Mitra Flora, 60 ml/plant, 120 ml/plant. The second factor is Moringa leaf extract consists of three levels, without extract of Moringa leaves, 75 ml/plant, 150 ml/plant. The result showed that there was no influence of interaction between Mitra Flora fertilizer and moringa leaf extract on all parameters observed, as well as the main influence of each factor of treatment either Mitra Flora fertilizer dosage or moringa leaf extract also did not occur on all parameters observed. Fertilizer dosage of Mitra Flora 60 ml per plant is the optimum dosage that gives the yield of mustard weighs 149.1 g per plant. The dose of moringa leaf extract of 150 ml per plant gives the best weave yield weighing 153 g per plant.